Sustainable construction management in education sector - Singh, Subhav; Dixit, Saurav; Varshney, Deekshant (International Journal of Engineering and Technology, 2018)
The purpose of the study is to understand and identify the current courses on sustainability in construction in leading universities in India. The study is conducted on pan India basis and different courses have been compared and results were drawn. The research is conducted using a structured questionnaire survey from the respondents through all over India. Keeping in mind the end goal to evaluate the heartiness of the course educational programs at School of civil engineering K R Mangalam University, a correlation was led with establishment’s offering comparable projects. The findings of the study conclude that the curriculum at School of civil engineering K R Mangalam University is effective in imparting sustainability concepts in the built environment domain. The students who have progressed towards the end of the course appeared to have achieved a good level of understanding of both the general and specific aspects of sustainability and its applications to the built environment. With expanding the effect of human survival on condition and unending civil argument of our duty towards who and what is to come, sustainability has made some amazing progress.